Hemolysis During Pediatric Extracorporeal Membrane Oxygenation: Associations With Circuitry, Complications, and Mortality. Issue 11 (November 2018) - Dalton, Heidi J.; Cashen, Katherine; Reeder, Ron W.; Berg, Robert A.; Shanley, Thomas P.; Newth, Christopher J. L.; Pollack, Murray M.; Wessel, David; Carcillo, Joseph; Harrison, Rick; Dean, J. Michael; Meert, Kathleen L.
Abstract : Objectives: To describe factors associated with hemolysis during pediatric extracorporeal membrane oxygenation and the relationships between hemolysis, complications, and mortality. Design: Secondary analysis of data collected prospectively by the Collaborative Pediatric Critical Care Research Network between December 2012 and September 2014. Setting: Three Collaborative Pediatric Critical Care Research Network-affiliated hospitals. Patients: Age less than 19 years and treated with extracorporeal membrane oxygenation. Interventions: None. Measurements and Main Results: Hemolysis was defined based on peak plasma free hemoglobin levels during extracorporeal membrane oxygenation and categorized as none (< 0.001 g/L), mild (0.001 to < 0.5 g/L), moderate (0.5 to < 1.0 g/L), or severe (≥ 1.0 g/L). Of 216 patients, four (1.9%) had no hemolysis, 67 (31.0%) had mild, 51 (23.6%) had moderate, and 94 (43.5%) had severe. On multivariable analysis, variables independently associated with higher daily plasma free hemoglobin concentration included the use of in-line hemofiltration or other continuous renal replacement therapy, higher hemoglobin concentration, higher total bilirubin concentration, lower mean heparin infusion dose, lower body weight, and lower platelet count. Using multivariable Cox modeling, daily plasma free hemoglobin was independently associated with development of renal failure during extracorporeal membrane oxygenation (defined as creatinine > 2 mg/dL [> 176.8 μmol/L] or use of in-line hemofiltration or continuous renal replacement therapy) (hazard ratio, 1.04; 95% CI, 1.02–1.06; p < 0.001), but not mortality (hazard ratio, 1.01; 95% CI, 0.99–1.04; p = 0.389). Conclusions: Hemolysis is common during pediatric extracorporeal membrane oxygenation. Hemolysis may contribute to the development of renal failure, and therapies used to manage renal failure such as in-line hemofiltration and other forms of continuous renal replacement therapy may contribute to hemolysis. Hemolysis was not associated with mortality after controlling for other factors. Monitoring for hemolysis should be a routine part of extracorporeal membrane oxygenation practice, and efforts to reduce hemolysis may improve patient care. Abstract : Supplemental Digital Content is available in the text.